Paediatric Gastrointestinal Endoscopy: European Society for Paediatric Gastroenterology Hepatology and Nutrition and European Society of Gastrointestinal Endoscopy Guidelines. Issue 1 (January 2017) - Thomson, Mike; Tringali, Andrea; Dumonceau, Jean-Marc; Tavares, Marta; Tabbers, Merit M.; Furlano, Raoul; Spaander, Manon; Hassan, Cesare; Tzvinikos, Christos; Ijsselstijn, Hanneke; Viala, Jérôme; Dall'Oglio, Luigi; et al.
Abstract : ABSTRACT: This guideline refers to infants, children, and adolescents ages 0 to 18 years. The areas covered include indications for diagnostic and therapeutic esophagogastroduodenoscopy and ileocolonoscopy; endoscopy for foreign body ingestion; corrosive ingestion and stricture/stenosis endoscopic management; upper and lower gastrointestinal bleeding; endoscopic retrograde cholangiopancreatography; and endoscopic ultrasonography. Percutaneous endoscopic gastrostomy and endoscopy specific to inflammatory bowel disease has been dealt with in other guidelines and are therefore not mentioned in this guideline. Training and ongoing skill maintenance are to be dealt with in an imminent sister publication to this.